Periodontitis and Cognitive Decline in Alzheimer’s Disease - Ide, Mark; Harris, Marina; Stevens, Annette; Sussams, Rebecca; Hopkins, Viv; Culliford, David; Fuller, James; Ibbett, Paul; Raybould, Rachel; Thomas, Rhodri; Puenter, Ursula; Teeling, Jessica; et al. (PLOS ONE, 2016)
Periodontitis is common in the elderly and may become more common in Alzheimer’s disease because of a reduced ability to take care of oral hygiene as the disease progresses. Elevated antibodies to periodontal bacteria are associated with an increased systemic pro-inflammatory state. Elsewhere raised serum pro-inflammatory cytokines have been associated with an increased rate of cognitive decline in Alzheimer’s disease. We hypothesized that periodontitis would be associated with increased dementia severity and a more rapid cognitive decline in Alzheimer’s disease. We aimed to determine if periodontitis in Alzheimer’s disease is associated with both increased dementia severity and cognitive decline, and an increased systemic pro inflammatory state. In a six month observational cohort study 60 community dwelling participants with mild to moderate Alzheimer’s Disease were cognitively assessed and a blood sample taken for systemic inflammatory markers. Dental health was assessed by a dental hygienist, blind to cognitive outcomes. All assessments were repeated at six months. The presence of periodontitis at baseline was not related to baseline cognitive state but was associated with a six fold increase in the rate of cognitive decline as assessed by the ADAS-cog over a six month follow up period. Periodontitis at baseline was associated with a relative increase in the pro-inflammatory state over the six month follow up period. Our data showed that periodontitis is associated with an increase in cognitive decline in Alzheimer’s Disease, independent to baseline cognitive state, which may be mediated through effects on systemic inflammation.